2005
DOI: 10.1002/cncr.21390
|View full text |Cite
|
Sign up to set email alerts
|

Educational and social late effects of childhood cancer and related clinical, personal, and familial characteristics

Abstract: The protein human CC chemokine ligand 2 (CCL2, also known as monocyte chemoattractant protein 1 or MCP‐1) has been synthesized using a combination of solid phase peptide synthesis (SPPS) and native chemical ligation (NCL). The thioester‐peptide segment was synthesized using the sulfonamide safety‐catch linker and 9‐fluorenylmethoxycarbonyl (Fmoc) SPPS, and pseudoproline dipeptides were used to facilitate the synthesis of both CCL2 fragments. After assembly of the full‐length peptide chain by NCL, a glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
270
4
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 288 publications
(303 citation statements)
references
References 62 publications
21
270
4
8
Order By: Relevance
“…Leukemia survivors had poorer results for numeracy and reading tests than for writing. Unlike the results reported by Barrera et al, 13 neuroblastoma survivors in our study were not more likely to have academic problems; however, in agreement with Mitby et al, 15 they did use special education services more often. Unfortunately, in our study there, were insufficient numbers of survivors in diagnostic subgroups or with multiple Original Article .118…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Leukemia survivors had poorer results for numeracy and reading tests than for writing. Unlike the results reported by Barrera et al, 13 neuroblastoma survivors in our study were not more likely to have academic problems; however, in agreement with Mitby et al, 15 they did use special education services more often. Unfortunately, in our study there, were insufficient numbers of survivors in diagnostic subgroups or with multiple Original Article .118…”
Section: Discussionsupporting
confidence: 86%
“…Other studies that have assessed different populations with fewer outcome measures have reported an excess risk of poor educational achievement among survivors of CNS tumors and leukemia. 9,13,15 The reciprocal pattern of enrollment of survivors in English and Communications 12 and the reduced enrollment of survivors in Math 12, coupled with the lack of difference in Grade 12 examination results between survivors and the student sample, suggest that there may be self-selection for ability in these subjects. In particular, the findings for Math 12 most likely reflect difficulties in mathematic skills; mathematic deficits and poor arithmetic achievement have been reported previously among childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations